Association between early bronchiolitis and the development of childhood asthma: a meta-analysis. Issue 5 (28th May 2021) - Wang, Guizuo; Han, Dong; Jiang, Zhengdong; Li, Manxiang; Yang, Shumei; Liu, Lu
Abstract : Objective: Early life bronchiolitis has been hypothesised to be associated with the subsequent risk of persistent wheezing or asthma. However, the link remains controversial. The objective of our study was to evaluate the association between bronchiolitis before 2 years of age and the late-onset wheezing/asthma. Design: Systematic review and meta-analysis. Methods: PubMed, Embase and Web of Science databases were systematically searched for studies published between 1955 and January 2020. Meanwhile, we also checked through the reference lists of relevant articles to see whether these references included reports of other studies that might be eligible for the review. Cohort and case–control studies assessing the association between early-life bronchiolitis and late-onset wheezing/asthma were included in this meta-analysis. Data were extracted by two independent reviewers. Results were pooled using a random-effects model or fixed-effects model according to the heterogeneity among studies. Results: 32 original articles with 292 844 participants, which met the criteria, were included in this meta-analysis. Bronchiolitis before 2 years of age was associated with an increased risk of subsequent wheezing/asthma (relative risk=2.46, 95% CI 2.14 to 2.82, p<0.001). After categorising studies into different groups based on age at the end of follow-up, geographical region and study quality, the association still remained significant. Conclusions: The meta-analysis indicates an association between bronchiolitis before 2 years of age and the wheezing/asthma in later life. Well-designed and highly standardised prospective studies that better address bias due to potential confounding factors are needed to validate the risk identified in our meta-analysis. PROSPERO registration number CRD42018089453.